Neutrophilic Dermatoses (Springer International Publishing, 2018)
This book provides an in depth overview of Neutrophilic Dermatoses, a group of diseases that includes Sweet's syndrome, pyoderma gangrenosum and subcorneal pustular dermatosis. Although there are still some gaps in the knowledge, it is now clear that their pathophysiology implies that mechanisms associated with auto-inflammation are involved, while many of these dermatoses occur in the setting of other systemic inflammatory diseases (colitis, arthritis) and of malignancies (blood malignancies, solid cancers). As such it is an important area of study within internal medicine. Neutrophilic Dermatoses represents an extensive clinical review of the group of diseases and is a critical resource for all medical professionals managing these patients, including clinicians in dermatology, gastro-enterology,, rheumatology, hematology, and internal medicine.